Removal of Tartrazine Dye onto Mixed‐Waste Activated Carbon: Kinetic and Thermodynamic Studies. Issue 12 (22nd April 2014) - Habila, Mohamed Abdelaty; ALOthman, Zeid Abdullah; Ali, Rahmat; Ghafar, Ayman Abdel; Hassouna, Mohamed Slah El‐Din
<x xml:space="preserve">Abstract</x> Numerous studies have been performed on the conversion of individual types of waste into activated carbon (AC). However, this study focused on the evaluation of the simultaneous conversion of different types of wastes (palm, paper, and plastic wastes) into AC via copyrolysis. The tartrazine adsorption capacity onto the produced AC was optimized. The results showed that the carbon content of the AC improved as the calcium hydroxide concentration varied from 0.0 to 2.0 mol L−1. In addition, the volatile matter and ash content were reduced as the concentration of calcium hydroxide was increased from 0.0 to 2.0 mol L−1. The tartrazine adsorption capacity of the prepared AC samples increased as the calcium hydroxide concentration increased from 0.5 to 2 mol L−1 at a carbonization temperature of 400°C for 2 h and a final activation temperature of 500°C for 1 h. Effective adsorption occurred at pH 2. The maximum adsorption capacity (74.9 mg g−1) was obtained with a contact time of 300 min and an initial tartrazine concentration of 150 ppm. The adsorption kinetics of tartrazine were modeled with pseudo‐first order, pseudo‐second order, and intraparticle diffusion models, which revealed that the tartrazine adsorption onto the AC showed a best fit with the pseudo‐second order kinetic model. The thermodynamic parameters ΔG0, ΔH0, and ΔS0 indicated that the adsorption of tartrazine onto the AC was spontaneous and endothermic. The values of ΔG0 were between −1.3 and −2.3 kJ mol−1, and the ΔH0 and ΔS0 values, in the temperature range of 25–50°C, were 9.12 kJ mol−1 and 35.5 J mol−1 K−1, respectively. In general, the thermodynamic parameters indicate that the adsorption is spontaneous and endothermic.